Status of shallow wells along major rivers of the Kathmandu Valley, Central Nepal - Bajracharya, Ramita; Tamrakar, Naresh Kazi; Shrestha, Manish; Bohara, Bimal (Journal of Nepal Geological Society, 2018)
Groundwater is one of the important natural resources to which people of the Kathmandu Valley rely on for their daily purpose. The rate of extraction of groundwater from shallow as well as deep aquifers has increased in the river corridor with the increased urbanization towards the major river corridors in the valley. Wells located within 100 m from the rivers of the Kathmandu Valley were focused in the present study. Altogether 237 wells were recorded from the Bagmati, Manahara and the Bishnumati River corridors of the northern Kathmandu basin, and the Dhobi, Hanumante, Godavari, Kodku, Nakhu and the Balkhu Khola corridors of the southern Kathmandu basin. This research was based on field measurements of well dimension (well diameter, well depth and water level depth) and physical parameters (electrical conductivity, dissolve oxygen, pH and temperature) in April and August of year 2017. The lowest water level was measured in the Nakhu Khola and the highest was measured in the Dhobi Khola in dry season. Average EC ranged between 614.2 μS/cm and 1123.9 μS/cm in dry season, and between 613.0 μS/cm and 916.1 μS/cm in wet season. DO also varied from 1.46 mg/L to 2.46 mg/L in dry season and increased to 1.67–2.53 mg/L in wet season. The lower DO and higher EC in the Balkhu Khola corridor indicates the most contaminated wells in the Kathmandu Valley. Average values of pH and temperature increased in wet season compared to dry season. Average high values of EC and low values of DO were recorded within 30 m distance from the rivers, and EC increased and DO decreased as the distance from river channel increased.